Non-metallic doped GeC monolayer: tuning electronic and photo–electrocatalysis for water splitting - Ni, Xiangxiang (Frontiers in Chemistry, 2024)
We conducted the first principles study on the electronic, magnetic, and optical characteristics of non-metallic atoms (B, C, F, H, N, O, P, S, Si) doped in single layer GeC. The findings indicate that introduction of various non-metallic atoms into monolayer GeC leads to modifications in its band structure properties. Different non-metallic atoms doped the single layer GeC will produce both magnetic and non-magnetic properties. B-, H-, N-, and P-doped GeC systems exhibit magnetic properties, while C-, F-, O-, S-, and Si-doped single layer GeC systems exhibit non-magnetic properties. Different non-metallic doped single layer GeC will produce semiconductor, semimetallic, and metallic properties. The C-, N-, O-, P-, S-, and Si-doped GeC systems still exhibit semiconductor properties. The H-doped GeC system exhibits semimetallic properties, while the B-and F-doped GeC systems exhibit metallic properties. Other than that, the doping of B, H, N, and P atoms can modulate the magnetism of single layer GeC. Subsequently, we studied the influence of the doping behavior on the work function, wherein the work function of the single layer GeC system doped with P atom is very small, indicating that its corresponding doping system (P-doped GeC system) can produce a good field emission effect. In the optical spectrum, the doped systems have a certain influence in the far ultraviolet region. Furthermore, our results show that S-and Si-doped single layer GeC systems are conducive to photocatalysis compared to single layer GeC system.